A naturalistic observational study on food interactions and indicators of healthy and unhealthy eating in White-European and Latinx families - Rodríguez Arauz, Gloriana (2022)
This study examined the relationships between self-reported and behavioral authoritative parenting practices and indicators of healthy and unhealthy eating in a sample of 29 families with a child 3–5 years of age (14 Latinx families, 15 White-European families). This study used self-report measures and an innovative audio recording device to track caregiver-child interactions in natural environments. Main findings of this study include that Latinx caregivers compared to White-European caregivers were less warm and less likely to encourage their children to eat, both at the behavioral level and the caregiver-report level. In the case of Latinx caregivers only, behavioral praise and warmth were related to lower consumption of sweets and sweetened beverages. Taken together, the findings of this study offer valuable insights into the nature of authoritative food parenting in naturalistic settings. Findings and implications for culturally relevant interventions are discussed.